Storytelling approaches in magazine radio programs in Argentina: description and analysis of radio genres - Martínez-Costa, María del Pilar (2018)
The study focuses on storytelling techniques applied in prime-time radio magazines in Argentina. The article analyzes the four leading audience programs at the beginning of this decade. Argentina has a concentrated market, radio penetration reaches 70% and prime time is between 10:00 and 12:00 AM. By means of content analysis of 160 hours of radio programming, use of different radio genres is analyzed in a wide range of prime time programs from news and opinion to fiction and entertainment, including audience participation. The comparative study of frequency and length of each genre, in different programs and different broadcast bands, shows the relative importance of each and the level of use along the continuity which define magazine as a radio format.